A novel modeling method for the mechanical behavior of 3D woven fabrics considering yarn distortion. (10th November 2022) - Li, Mengran; Liu, Kai; Ge, Jingran; Xie, Junbo; Liu, Zengfei; Zhang, Binbin; Huang, Jian; Liang, Jun
Abstract: Three-dimensional woven fabrics feature complex meso-architectures, such as yarn torsion and cross-section variation. This paper aims to developing a novel numerical modeling method to simulate the mechanical behaviors of reinforcements considering realistic yarn geometries. The initial as-woven unit cell is first simulated by the digital element analysis. A reconstruction algorithm is then used to generate mesoscale high-fidelity solid geometric models from digital chains. Fiber directional orientation within torsional yarns of the high-fidelity model is described by a digital-chain tracing method and analyzed in detail. Furthermore, based on the high-fidelity model, a hyper-elastic constitutive model is employed for the numerical analysis of the mechanical properties of reinforcements. The finite element analysis (FEA) of transverse compression, tensile deformation and in-plane shearing deformation combined with in-situ Micro-CT experiments are carried out to verify the method. The proposed method agrees well with experimental tests. Defining fiber orientations of torsional yarns using the digital-chain tracing method leads to more accurate simulation results. The developed numerical method can be extended for the composites design and structure optimization due to its high-fidelity simulation capabilities. Graphical abstract: Image 1